2018
DOI: 10.1002/csr.1654
|View full text |Cite
|
Sign up to set email alerts
|

Millennials' green consumption behaviour: Exploring the role of social media

Abstract: Several studies have investigated millennials' perceptions of sustainable products, and the factors that make these products appealing. Yet insight into the green purchase intentions of this demographic and influencing factors is limited. This study investigates the influence of social media usage and online interpersonal influence on green purchase intentions among millennials in the USA. In addition, the study considers how the cultural dimensions of individualism–collectivism and masculinity–femininity mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
102
2
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(148 citation statements)
references
References 53 publications
9
102
2
4
Order By: Relevance
“…Social media and online influencers could be seen as a booster of the ZW principles on the household level. Bedard and Tolmie (2018) found a positive relationship between levels of social media usage and levels of green purchase intentions. They also found that online interpersonal influence has an impact on green purchase intentions.…”
Section: Determinants Of the Zero Waste Consumer Lifestylementioning
confidence: 86%
“…Social media and online influencers could be seen as a booster of the ZW principles on the household level. Bedard and Tolmie (2018) found a positive relationship between levels of social media usage and levels of green purchase intentions. They also found that online interpersonal influence has an impact on green purchase intentions.…”
Section: Determinants Of the Zero Waste Consumer Lifestylementioning
confidence: 86%
“…For instance, for millennials from high power distance and uncertainty avoidance countries (e.g. Russia) luxury managers should invest additional resources to social media use, social media strategies, investing in influencers, offering exclusive promotions (Bedard and Tolmie, 2018) and comprehensive information. Luxury companies could benefit by facilitating interactions between company and consumers through including a hyperlink on their website with consumers' trial experiences, assessment of their brands and ratings (Bei et al, 2004;Chen et al, 2016;Dellarocas, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…These recommendations can help them to develop brand attitudes. Moreover, as millennials post their item ratings, reviews and online experiences (Bedard and Tolmie, 2018) they are often well-informed on items that being bought by others. As was found in prior studies, susceptibility to informative influence can be highly impactful in decision-making processes and it has a significant effect on attitude toward the brand (Gentina et al, 2016;Chen et al, 2016).…”
Section: Susceptibility To Informative Influencementioning
confidence: 99%
“…Consequently, millennials have become a remarkable group for study given their distinctive behavior as compared to other generations [7], their sharing of common values [24,25], enjoyment of life experiences [26], pursuance of specific motivations [3,5,14,27], and purchasing behavior [24,28]. Millennials are characterized as having a higher education level than other generations [1,29] or by the intensive use and adaptation of technology in their daily lives [17,28,30,31]. This consumer group exhibits different food purchasing behavior from other groups, are highly aware of their eating habits [7,31], and are more likely to come across an innovative food product on the market in a near future [24].…”
Section: Food Naturalness and Millennials' Behaviormentioning
confidence: 99%